Diagnostic Systems For Energy Equipments - Babak, Vitalii P.; Babak, Serhii V.; Myslovych, Mykhailo V.; Zaporozhets, Artur O.; Zvaritch, Valeriy M. (Studies in Systems, Decision and Control, 2020)
X, 133 p. 52 illus., 8 illus. in color.